Optimal use of plasma and urine BK viral loads for screening and predicting BK nephropathy. Issue 1 (December 2016) - Boan, Peter; Hewison, Christopher; Swaminathan, Ramyasuda; Irish, Ashley; Warr, Kevin; Sinniah, Rajalingam; Pryce, Todd; Flexman, James
Abstract Background BK virus is a polyoma virus causing renal allograft nephropathy. Reduction of immunosuppression with the early recognition of significant BK viral loads in urine and plasma can effectively prevent BKV associated nephropathy (BKVN), however the optimal compartment and frequency of BK viral load measurement post renal transplantation are undetermined. Our purpose was to examine time to detection and viral loads in urine compared to plasma, and establish viral load cut-offs associated with histological BKVN. Methods We performed a retrospective analysis of the BKV screening frequency and compartment(s) of 277 adult renal transplant recipients (RTR). Results BKVN was histologically diagnosed in 17 (6.1 %) RTR. In cases where both urine and plasma were tested fortnightly for 6 months (n = 53), BKV was detected in the urine 29 days earlier than plasma. Fortnightly (n = 72) versus 3-monthly (n = 78) testing demonstrated that BKV was detected in the urine significantly earlier (median 63 versus 97 days, p = 0.001) and at a lower level (median 3.27 versus 6.71 log10 c/mL, p < 0.001) with more frequent testing, but this difference was not evident in plasma first detection (80 versus 95 days, p = 0.536) or first positive viral load (3.18 versus 3.30 log10 c/mL, p = 0.603). The optimum cut-off BK viral load for histological diagnosis of BKVN was 4.10 log10 c/mL for the first positive urine, 3.79 log10 c/mL for the first positive plasma, 9.24 log10 c/mL for the peak urine, and 4.53 log10 c/mL for the peak plasma. Conclusions Frequent urinary BK viral load screening for the prevention of BKVN is suggested due to its high sensitivity and earlier detection.